2020
DOI: 10.3389/fphar.2020.00298
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Danhong Injection on Cerebral Ischemia-Reperfusion Injury in Rats by Activation of the PI3K-Akt Pathway

Abstract: Many traditional Chinese medicines, including Danhong injection (DHI), can be used to treat cerebral ischemia-reperfusion injury and have neuroprotective effects on the brain; however, few studies have explored the mechanism by which this effect is generated. In this study, we investigated the neuroprotective effect of DHI against cerebral ischemia-reperfusion injury mediated via the PI3K-Akt signaling pathway. After establishing the model of middle cerebral artery occlusion (MCAO), 60 male Sprague-Dawley rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 57 publications
(52 reference statements)
5
39
0
Order By: Relevance
“…PI3K/AKT pathway is a common signaling pathway associated with cell proliferation and migration [27]. We studied its changes when DHI acts on RSC96 cells, and found that PI3K/AKT is signi cantly activated, which was consistent with Zhou's ndings in atherosclerosis [28] and Feng's study on cerebral ischemia/reperfusion injury [29] in which DHI activates the PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 78%
“…PI3K/AKT pathway is a common signaling pathway associated with cell proliferation and migration [27]. We studied its changes when DHI acts on RSC96 cells, and found that PI3K/AKT is signi cantly activated, which was consistent with Zhou's ndings in atherosclerosis [28] and Feng's study on cerebral ischemia/reperfusion injury [29] in which DHI activates the PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 78%
“…DHI has been used extensively in the clinical treatment of coronary heart disease and acutely cerebral infarction for many years (He et al, 2012). More experimental evidences show that DHI exerts diverse pharmacological properties by modulating multiple molecular targets (Feng et al, 2019), including recovery of cerebral glucose metabolism by serial 18 F-labeled fluoro-2-deoxyglucose ( 18 F-FDG)-micro positron emission tomography (PET) imaging and enhancing neurogenesis (Wang et al, 2014), angiogenesis-promoting actions by up-regulating expressions of the related factors of angiogenesis (Wan et al, 2018), and antiapoptotic by activating phosphatidylinositol 3-kinase-protein kinase B (PI3K-Akt) signaling pathway (Feng et al, 2020). Clinically, a network meta-analysis of randomized controlled trials found that DHI combined with other regimens had the highest effective rate in the treatment of acute cerebral infarction (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…e PI3K-Akt signalling pathway has a neuroprotective effect in MCAO rats through inhibition of cell apoptosis [48,49]. By activating the PI3K-Akt signalling pathway, Danhong injection increases the expression of antiapoptotic factors, inhibits the expression of apoptotic factors, and exerts a neuroprotective effect in MCAO rats [50]. Electroacupuncture reduces the cerebral infarct volume and the activation of cleaved caspase-3 in MCAO rats by activating the PI3K-Akt signalling pathway [51].…”
Section: Discussionmentioning
confidence: 99%